Optical Coherence Tomography Angiography, Elastography, and Attenuation Imaging for Evaluation of Liver Regeneration - Svetlana Rodimova; Ekaterina Gubarkova; Nikolai Bobrov; Ilya Shchechkin; Vera Kozlova; Natalia Zolotova; Arseniy Potapov; Elena Kiseleva; Grigory Gelikonov; Natalia Gladkova; Vladimir Zagainov; Elena Zagaynova; et al. (Diagnostics)
Background/Objectives: As a result of metabolic changes and the disruption of tissue architecture and microcirculation, the regenerative potential of the liver decreases with violations at both micro and macro levels. The development of intraoperative approaches for assessing its regenerative potential is important for reducing the risk of the occurrence of post-resection liver failure. In this study, we used multimodal optical coherence tomography (MM OCT), a combination of three optical coherence tomography modalities—OCT–angiography (OCTA), attenuation coefficient mapping, and OCT–elastography (OCE) to provide real-time three-dimensional and label-free assessment of changes in microcirculation, and in the structure and stiffness of the liver during regeneration. Methods: In our study, the regeneration of a healthy liver was induced by 70% partial hepatectomy. Monitoring of changes was carried out on the 0 (normal liver), 3rd and 7th day of regeneration using modalities of MM OCT. OCT offers the benefits of higher resolution and specificity compared with other clinical imaging modalities, and can be used, even intraoperatively. Results: By the 3rd day of liver regeneration, a decreased density of all observable vessels, together with increased values of the liver tissue’s attenuation coefficient and stiffness, was revealed compared to their initial state. However, by the 7th day, the studied parameters tended to return to their normal values, except that the density of large-caliber vessels continued to increase further. Histological and biochemical blood analysis methods were used to verify the MM OCT data. Conclusions: Such data are a first step towards further investigation of liver regeneration in pathology, and, taken in perspective, this should serve as a basis for predictive intraoperative assessment of the regenerative potential of the liver in a clinical setting.